MODERNIZING ZAKAT,INFAK AND SHADAQAH GOVERNANCE: INSIGHTS FROM DIFFUSION,INSTITUTIONAL, AND CONTINGENCY THEORIES - Suwito, Suwito; Kamal, Muhammad; AR Mahdi, Suriana; Sharma, Mala (EL DINAR: Jurnal Keuangan dan Perbankan Syariah, 2025)
This study investigates the modernization of ZIS governance in Ternate City Indonesia, focusing on Baitul Maal Hidayatullah (BMH) as a case study. The primary aim is to formulate innovative models and strategies that integrate technological solutions with community-based approaches to enhance the effectiveness of zakat management. Adopting a qualitative phenomenological method, the research draws on in-depth interviews with zakat managers and stakeholders involved in digital transformation initiatives. Findings reveal that the application of technology, such as blockchain-based systems, mobile applications, and digital payment platforms, has significantly increased the efficiency, transparency, and accountability of zakat operations. BMH, for instance, achieved 100% of its fundraising target through digital channels, compared to only 50–60% via conventional methods. At the same time, challenges persist, including limited access to technology and low digital literacy in rural areas, prompting the adoption of a hybrid model that combines manual and digital services to maintain inclusivity. The study emphasizes the importance of technology as a driver of modern zakat governance while highlighting the need for adaptive strategies aligned with local socio-cultural contexts. These findings contribute to the broader discourse on Islamic social finance and provide practical insights for enhancing trust, inclusivity, and sustainability in zakat institutions.